PENGARUH KOMPENSASI, MOTIVASI DAN BUDAYA ORGANISASI TERHADAP DISIPLIN KERJA KARYAWAN PT. RIAU POS INTERMEDIA PEKANBARU - Irma Wardhani; Machasin '; Chairul Amsal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This research aim to know Influence of Compensation, Motivation and Organizational Culture to Discipline Work Employees At PT. Riau Pos Intermedia Pekanbaru. As for becoming population in this research is all laboring employees at PT. Riau Pos Intermedia Pekanbaru. Population in this research is all employees to in PT. Riau Pos Intermedia Pekanbaru amounting to 84 people. In intake of writer sampel use census method to all employees. Date analysis the used [is] descriptive analysis, despitefully also use quantitative analysis that is using doubled linear regresi constructively program of SPSS version 18.00. From result of examination which have been conducted, test of regresi simultan indicate that Compensation, Motivation and Organizational Culture have an effect on to Discipline Work Employees of PT. Riau Pos Intermedia Pekanbaru. Result of Test of parsial indicated that Compensation variable, Motivation and Organizational Culture effect to Discipline Work Employees at PT. Riau Pos Intermedia Pekanbaru.Keyword: Compensation, Organizational Culture, Motivation, And Discipline Work